Ciclagem de nutrientes e produtividade de grãos em sucessões de culturas sob sistema plantio direto - Fiorin, Jackson Ernani (2008)
The no-tillage adoption combined with the presence of crop residues on soil surface and minimum soil disturbance increase the soil organic matter content, that associated with broadcast fertilization, change the nutrient dynamic and its relationship with plant nutrition. This study was carried out in a long term experiment (1997 to 2007) in Cruz Alta (RS) aim to select cropping systems efficient in nutrient cycling of N,P and K and maintain crop yield under no-tillage. The experimental design was randomized blocks with four replications. The cropping systems were composed by cover crops and cash crops: 1) radish oil/maize/radish oil/wheat/ soybean; 2) black oat/maize/black beans/wheat/soybean; 3) common vetch/maize/ radish/wheat/soybean; 4) common vetch/maize/sunhemp/wheat/soybean; 5) common vetch/maize/radish/wheat/soybean; 6) common vetch/maize/sunhemp/ wheat/soybean. In treatments 3 and 4 were applied 324 kg ha-1 P2O5 and K2O during the experimental period. The N fertilization wasn t used in all treatments. With the objective to evaluate the NPK fertilization response in 9 and 10th year were applied the N rates (0, 40, 80, 120 kg ha-1), P (0, 30, 60, 90 kg ha-1) and K (0, 30, 60, 90 kg ha-1) in maize and wheat. In soybean only residual effect was evaluated. The yields, nutrient balance trough inputs (biologic fixation of N and P and K mineral fertilization) and outputs (N, P and K exported by harvest), nutrient cycling (nutrients uptake by cover crops and commercial crops) was determined. The higher N input, nutrient uptake, nutrient exported in grain and corn, wheat and soybean yield were higher in cropping systems with legumes. The sucession of radish oil/radish oil and black oat/beans had lower N input, nutrient uptake, nutrient cycling, nutrient exported in grain and yield. The cropping systems with common vetch before maize and radish oil between maize and wheat were efficient in maintain the crop yield. The nutrient cycling had high relationship with crop yield. The cropping systems show different yield potential to the same content of soil nutrient. The increment of soil organic carbon among cropping systems ranged from 0.31 and 1.00 Mg ha-1 year-1. The carbon input were 31.7%, 20.4%, 19.5%, 14.8% and 13.7% to maize, summer cover crops, winter cover crops, soybean and wheat respectively in average of 8 years.